The Impact of BIM-based virtual and augmented reality interfaces on health and safety in construction projects: protocol for a systematic review - Alfredo Soeiro (2018)
The construction sector is notable for its interdisciplinary knowledge and complex interactions between different parties and the sector has been gradually adopting new methodologies to improve work and collaboration practices, such as the case of Building Information Modeling (BIM). A protocol for a systematic review is proposed to evaluate the effectiveness of virtual reality techniques in the Architectural, Engineering, Construction and Operations sector. The search will be carried out in the reference databases for the field. One of the main outcomes of this study is to assess the effectiveness of virtual reality tools implemented in construction projects at the same time it will try to estimate the cost of the equipment and the implementation of the intervention and if any other mentioned cost might be related to risk reduction or better performance. This protocol is registered in PROSPERO under the code of PROSPERO CRD42018085845.